PERAN DINAS LINGKUNGAN HIDUP KOTA TANGERANG DALAM PENANGANAN SAMPAH (STUDI UPT WILAYAH TIMUR) - Okky Mirwandi; Doddy Mulyono (Gapenas Publisher, 2023)
The increasing number of migrants from outside the region has resulted in an increase in the volume of waste in the city. Waste management is an effort to prevent the volume of waste from having a negative impact on the environment. The local government takes over official duties to play a role in realizing policies and providing services directly to the community, as the Tangerang City Environmental Service is responsible for carrying out waste management as a form of realization of the mandate of the Mayor of Tangerang Regulation Number 144 of 2021 concerning Position, Organizational Structure, Duties and Functions and Office Work Procedures Tangerang City Environment. This study aims to describe the role of the Tangerang City Environmental Service regarding Waste Handling carried out in Tangerang City. Using qualitative research methods with descriptive analysis techniques. Data collection with documentation, namely collecting primary and secondary data through various sources. The results showed that the role of the Tangerang City Environmental Service was relatively high. From the two indicators to see the role of the agency, there are supporting factors, namely the formulation of policies in the form of rules marked by a work plan, clear vision and mission, SOP, and organizational structure. As for the inhibiting factors, namely the researchers saw a lack of facilities because the accumulation of waste on one land still depended on the Rawa Kucing TPA whose capacity was already overloaded, damage to supporting facilities, and socialization that was not comprehensive so that there were still people who did not sort waste from home. Therefore, the Tangerang City Environmental Service can increase active participation of the community in a sustainable manner in implementing the 3R movement by providing facilities and infrastructure for waste transportation and processing, waste alms movement, outreach/education on waste management, assistance/guidance of waste banks